2016
DOI: 10.1631/jzus.b1500181
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor and diarrhea-predominant irritable bowel syndrome (IBS-D): a potential therapeutic target?

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder characterized by recurrent abdominal pain or discomfort associated with abnormal bowel habits. Diarrhea-predominant IBS (IBS-D) is a major subtype of IBS, the predominant manifestations of which are abdominal pain and diarrhea. The pathogenesis of IBS-D remained unknown until recently. The effects of psychosocial stress, central hypervigilance, neuroendocrine abnormality, disturbed gastrointestinal motility, mucosal immune activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
1
21
0
2
Order By: Relevance
“…This remarkable long‐term hyperexcitability also can be observed after degranulation of MCs . Previous report demonstrated that NGF was involved in the modulation of visceral hyperalgesia and hypersensitivity in IBS patients and rat model of IBS . In the present study, changes of NGF, tryptase, and some pro‐inflammatory cytokines in MCs or BMMCs provided a molecular mechanism for IBS in visceral hypersensitivity processes.…”
Section: Discussionsupporting
confidence: 72%
“…This remarkable long‐term hyperexcitability also can be observed after degranulation of MCs . Previous report demonstrated that NGF was involved in the modulation of visceral hyperalgesia and hypersensitivity in IBS patients and rat model of IBS . In the present study, changes of NGF, tryptase, and some pro‐inflammatory cytokines in MCs or BMMCs provided a molecular mechanism for IBS in visceral hypersensitivity processes.…”
Section: Discussionsupporting
confidence: 72%
“…Impaired gut barrier exposes the mucosal and submucosal structures to intraluminal pathogens and noxious stimuli, causing low‐grade mucosal inflammation‐immune activation and sensitisation of visceral nociceptors such as TRPV1. Visceral hypersensitivity and impaired barrier function constitute the two important factors in IBS‐D pathogenesis, and also the main causes of symptoms such as abdominal pain, distension and diarrhoea …”
Section: Discussionmentioning
confidence: 99%
“…In addition, disturbed gastrointestinal motility is a risk factor for D-IBS, and ion channels including Na v 1.8 and Na V 1.9 may influence the contractile ability of these organs, suggesting that the development of D-IBS may require the active participation of ion channels. Since expression of Na v 1.8 and Na v 1.9 channels, as well as NGF were enhanced by SCN9A gene modification, this may lead to a novel direction for D-IBS treatment (5). Designer genetic recombination tools and mammalian genetic modification technology are currently novel, reliable and efficient methods to target genomic sequences, which may result in further advances in understanding of gene expression and its associated influence (23).…”
Section: Discussionmentioning
confidence: 99%
“…The concrete pathogenesis of IBS is multifaceted and not completely understood, however several risk factors for IBS have been identified including genetic, epigenetic, environmental and behavioral factors (2). The development of D-IBS is correlated with psychosocial stress, altered gut flora, intestinal barrier dysfunction, disturbed gastrointestinal motility, mucosal immune activation, visceral hypersensitivity, euro-endocrine abnormality and genetic susceptibility (5). There is still no agreement over optimal pharmacological treatment for D-IBS and as ion channels are important in gastrointestinal function, disrupted ion channels may result in disease, therefore the present study aimed to investigate whether a gene associated with ion channels may act as a novel target to treat the disease (4,6).…”
Section: Introductionmentioning
confidence: 99%